2014
DOI: 10.1155/2014/453940
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Rescues the MG63 Osteoblasts against the Effect of High Glucose on Proliferation

Abstract: Aims. To study the proliferation of osteoblasts and genes expression under normal glucose, high glucose, and metformin (Met). Methods. MG63 osteoblast-like cells were cultured in osteogenic medium supplemented with normal glucose (glucose 5.5 mmol/L) or high glucose (glucose 16.7 mmol/L) and metformin + high glucose (Met 300 μmol/L + glucose 16.7 mmol/L). Proliferation was detected with CCK-8 assay at days 1, 3, and 7. Real-time PCR and Western blot were performed to compare the expression of collagen I (Col I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
32
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 19 publications
7
32
2
Order By: Relevance
“…Metformin has been preferred the first‐line drug treatment for type 2 diabetes in clinical use . On one hand, some studies showed anti‐inflammatory effects of metformin in chronic inflammation disease .…”
Section: Discussionmentioning
confidence: 99%
“…Metformin has been preferred the first‐line drug treatment for type 2 diabetes in clinical use . On one hand, some studies showed anti‐inflammatory effects of metformin in chronic inflammation disease .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, indigenously prepared MF gel for the treatment of CP has shown DDR in periodontal pockets for patients with CP and patients with CP who are smokers 14,15 . In a recent in vitro study, MF aided in the proliferation of MG63 osteoblast‐like cells 16 …”
mentioning
confidence: 97%
“…14,15 In a recent in vitro study, MF aided in the proliferation of MG63 osteoblast-like cells. 16 In a previous study, efficacy of minocycline microspheres was evaluated in cases of moderate periodontitis with PD ‡5 mm (American Dental Association [ADA]/American Academy of Periodontology [AAP] type III) and advanced periodontitis with PD ‡7 mm (ADA/AAP type IV). 17 Minocycline microspheres showed a greater mean PD reduction compared with placebo treatment in cases with initial PD ‡7 mm.…”
mentioning
confidence: 99%
“…They induce osteoblast cells to promote early bone formation through AMP kinase (AMPK) activity . Moreover, in a recent in vitro study, metformin facilitated in the proliferation of MG63 osteoblast like cells . Thus, their action in stimulating bone formation has justified their use in the treatment of periodontal bone defects in chronic periodontitis.…”
Section: Introductionmentioning
confidence: 99%